A comparison of the transport requirements of different curbside waste collection systems in Denmark. (15th March 2019) - Zbib, Hani; Wøhlk, Sanne
Highlights: Transport requirements for different curbside waste collection systems are compared. Analysis based on data from six counties in Denmark and different degrees of sorting. Additional sorting leads to a significant increase in the transport requirements. Collection with multi compartment vehicles is most desirable. Transport requirements are affected by vehicle size, compression factors, and packing. Abstract: With an increased focus on recycling, local authorities need to adapt their systems for curbside collection of household waste to accommodate an increased degree of sorting of waste types. Therefore, it is essential to study the transport aspects of waste collection. In this paper, we analyze the driving requirements for curbside collection of household waste for different systems in the context of Denmark. We consider a Collect, then sort system, as opposed to two Sort, then collect systems using single and multi-compartment vehicles, and compare the systems among themselves, and to the collection for incineration system. Our approach consists of solving the underlying capacitated arc routing problems of each system, and comparing the transport requirements in terms of driven distance and number of routes across systems. Our findings show that an increased degree of sorting is synonymous with a significant increase in the driven distance and the number of routes. Moreover, we find that the sort, then collect by multi-compartment vehicles system outperforms the others in terms of driven distance, and that the sort, then collect by single compartment vehicles system outperforms the others in terms of number of routes. We found that three cost drivers affect the overall results: the change in the size of the vehicle, the compression factor inside the vehicles' compartments, and the packing of the vehicles' compartments.